Farmers’ Willingness to Pay for Climate Smart Agriculture in Flood Vulnerable Areas of Assam - Barman, Sundar; P.K. Neog (Indian Journal of Extension Education, 2024)
The current study was carried out during 2020 in flood vulnerable district of Assam to measure the farmers’ Willingness to Pay (WTP) for climate smart agriculture practices and factors likely to influence thereon. The study reveals that degree of farmers ‘willingness to pay was found high for ‘Stress Tolerance Varieties of rice(STVs)’, ‘Integrated Nutrient Management(INM)’ and ‘Integrated Pest Management(IPM)’ while low degree of WTP was found for ‘Vermicompost preparation and application(VC)’and ‘Minimum Tillage(MT)’.The highest average bidding value was recorded for STV(Rs.251.00) followed by INM(Rs.185.00) and IPM(Rs.174.13) while for VC and MT the average bidding value was Rs.158.63 and Rs 79.75 respectively. The LMR analysis confirmed that the selected explanatory variables expressed variation in willingness to pay for CSA practices about74%(R2=0.74).The variable ‘educational status’(x2),‘accessible to market’(x7)‘cropping intensity’(x9),‘adoption consistency’(x13) and ‘preferences to CSA practices’(x14)were found to have positive while variable ‘age’(x1) and ‘institutional contact’(x6) have negative and significant influence on WTP. Popularizing CSA practices available in the research front, various organizations (both public and private) in input and output chains should work together as a common entity so that farmers get necessary nurture for adoption of technologies.